Acute coronary syndromes and percutaneous coronary interventions - Bassand, J.-P. (Hämostaseologie, 2009)
Activation of the coagulation cascade and platelet functions occurs in ACS and may lead to subsequent thrombus formation, vessel occlusion, distal embolisation, myocardial ischaemia, necrosis and eventually death. Over the last 20 years, the outcome of ACS and PCI patients has considerably improved, thanks to better pharmacologic environment, urgent reperfusion in STEMI (ST elevation myocardial infarction), timely revascularisation in non-ST elevation ACS (NSTEACS) and improved PCI techniques, particularly widespread use of stents.In this context, bleeding was long considered as inherent to the modern therapeutic approach and without real consequences. Actually, bleeding has a strong impact on outcome, with a four- to five-fold increase in the rate of death, myocardial infarction and stroke at 30 days and six months. In addition, blood transfusion may have deleterious effects. Recent evidence shows that reduced risk of bleeding leads to a reduced risk of ischemic events (death, myocardial infarction and stroke).The exact mechanisms by which bleeding impacts on outcome are as yet poorly understood. The interruption of active treatment may play an important role. Activation of coagulation or inflammation in case of bleeding, and depletion of 2,3DPG and nitric oxide, inflammatory and immunologic reactions triggered by blood transfusion, are among the potential mechanisms.Prevention of bleeding has become as important as prevention of ischaemic events. Risk stratification for bleeding is as important as overall risk stratification for further ischaemic events. In patients at high risk of bleeding, appropriate choice and dosage of drugs, combinations of drugs, and the use of radial rather than femoral approach are essential components of bleeding prevention.
Keywords: Acute coronary syndrome; percutaneous coronary intervention